Influence of Polyvinyl Sulphonic Acid on the Thermodynamics of Clouding Behaviour of Non-Ionic Surfactant Tween 40 - Jadhav, V.B.; Patil, T.J. (Asian Journal of Chemistry, 2010)
The phenomenon of micellization of non-ionic surfactant Tween 40 has been studied through the influence of additives polyvinyl sulphonic acid in aqueous medium by measuring the cloud points of the pure surfactant and with polyvinyl sulphonic acid. The cloud points of pure surfactant Tween 40 found to be increased with increased [Tween-40]. The cloud points of mixed system shows same trends with increased [concentration of polyvinyl sulphonic acid]. The influence of polyvinyl sulphonic acid on the cloud point of Tween 40 is a clear indication that the phenomenon of clouding is associated with the different micelles coalescing. Considering cloud point as threshold temperature of the solubility, the thermodynamic parameters of clouding process (ΔGºcl, ΔHºcl and ΔSºcl) have been evaluated using "phase separation model". The phase separation results from micelle-micelle interaction. It is found that the overall clouding process is exothermic and ΔHºcl > TΔSºcl indicating that the process of clouding is guided by both enthalpy and entropy. This work supports the conjecture that the clouding is critical phenomenon rather than the growth of micelles. Findings of the present work supports to made the probable evidence of polymersurfactant interactions in aqueous medium.